MODEL PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN BERBASIS ISU-ISU KONTROVERSIAL DI MEDIA MASSA UNTUK MENINGKATKAN SIKAP DEMOKRASI MAHASISWA DAN IMPLIKASINYA BAGI MASYARAKAT MADANI - Muhibbin, Ahmad; Sumarjoko, Bambang (Jurnal Pendidikan Ilmu Sosial, 2016)
ABSTRACT The study aims to describe 1) civics education learning in Higher Education in relation to democracy attitude and its implication to civilized community, 2) a model design of tentative civics education (PKn) learning, 3) a learning model of PKn as its reference, and 4) a model draft of PKn learning. This research used a qualitative approach with case study pattern. The data gathering technique employed an in-depth interview, observation, and documentation. The data validation applied a triangulation technique, member checking and collegial/peer   discussion. The data analysis used an interactive model. The results of the study show that 1) the PKn learning has not been working on the students’ democracy attitude development and its implication for a religious and civilized community so that it needs a paradigmatic dynamics of the learning in Higher Education. 2) the tentative model design include (a) the lecturers presented the controversial issues with the video/slide, (b) they explained the students about various problems, (c) they evaluated what the students has understood and has not understood  about them, (d) they developed an alternative solution with small groups, (e) each group presented the results of discussion, (f) they developed the materials that would be learnt more deeply and facilitated based on the concepts stated by each group; (g) they concluded  and closed the learning activity. 3) The model of controversial issues-based PKn learning was modified with active learning. 4) The model draft intended to the students’ democracy attitude development and its implication to civilized community covers (a) a-perception, (b) the groups’ presentation by discussing the controversial issues, (c) class discussion with active learning modification, (d) confirmation, and (e) closing.